Pelagic Habitat Partitioning of Late-Larval and Juvenile Tunas in the Oceanic Gulf of Mexico - Pruzinsky, Nina M.; Milligan, Rosanna J.; Sutton, Tracey T. (Frontiers in Marine Science, 2020)
Tunas are ecologically important in pelagic ecosystems, but due to their high economic value, large-bodied species are overfished. Declines in fishery landings of large-bodied tuna species in the Gulf of Mexico (GoM) are expected to increase fishing pressures on unmanaged, small-bodied tuna species, whose life history traits are less known. While predicting spawning stocks and recruitment success typically focuses on estimates of larval abundances, juveniles may provide a better estimate of future adult stock sizes, as they are more likely to survive to adulthood because mortality rates scale inversely with body size. However, distributional studies on juveniles are rare, leading to a gap in our understanding of tuna ecology. In the present study, tuna early life stages were collected across the GoM from January-September 2011. The size class examined in this study, representing large larvae and small juveniles, is larger than that of previous larval tuna studies in the GoM. Faunal composition, abundance, frequency of occurrence, and diel catchability were investigated. Generalized additive models (GAMs) were used to examine spatiotemporal distributions of the family Scombridae and the three most-abundant tuna species in the GoM’s epipelagic waters with respect to location, oceanographic features, and temporal change. In total, 11 of the 16 scombrid species inhabiting the GoM were collected, with small-bodied tuna species (Euthynnus alletteratus, Thunnus atlanticus, Auxis thazard) dominating the assemblage. Overall, scombrids were caught at higher abundances and frequencies at night than during the day, demonstrating that nighttime sampling generates a more accurate representation of faunal abundance and distribution. Abundance and presence-absence GAMs identified a coastal group (E. alletteratus and A. thazard) associated with productive continental shelf/slope environments (low salinity, higher chlorophyll a concentrations, nearer to shelf break) and an oceanic group (represented by T. atlanticus) associated with offshore, oligotrophic habitats (high salinity, lower chlorophyll a concentrations, further from shelf break). These results demonstrate that over a broad spatiotemporal domain, large larvae and juvenile tunas partition pelagic habitat on the mesoscale in addition to the temporal partitioning of adult spawning. These factors are important for spatially and temporally explicit modeling aimed at predicting tuna stock sizes.